NGTS clusters survey – III. A low-mass eclipsing binary in the Blanco 1 open cluster spanning the fully convective boundary. Issue 4 (7th September 2021) - Smith, Gareth D; Gillen, Edward; Queloz, Didier; Hillenbrand, Lynne A; Acton, Jack S; Alves, Douglas R; Anderson, David R; Bayliss, Daniel; Briegal, Joshua T; Burleigh, Matthew R; Casewell, Sarah L; Delrez, Laetitia; et al.
ABSTRACT: We present the discovery and characterization of an eclipsing binary identified by the Next Generation Transit Survey in the ∼115-Myr-old Blanco 1 open cluster. NGTS J0002−29 comprises three M dwarfs: a short-period binary and a companion in a wider orbit. This system is the first well-characterized, low-mass eclipsing binary in Blanco 1. With a low mass ratio, a tertiary companion, and binary components that straddle the fully convective boundary, it is an important benchmark system, and one of only two well-characterized, low-mass eclipsing binaries at this age. We simultaneously model light curves from NGTS, TESS, SPECULOOS, and SAAO, radial velocities from VLT/UVES and Keck/HIRES, and the system's spectral energy distribution. We find that the binary components travel on circular orbits around their common centre of mass in P orb = 1.098 005 24 ± 0.000 000 38 d, and have masses M pri = 0.3978 ± 0.0033 M⊙ and M sec = 0.2245 ± 0.0018 M⊙, radii R pri = 0.4037 ± 0.0048 R⊙ and R sec = 0.2759 ± 0.0055 R⊙, and effective temperatures T_pri=3372 ^+44_-37 K and T_sec=3231 ^+38_-31 K. We compare these properties to the predictions of seven stellar evolution models, which typically imply an inflated primary. The system joins a list of 19 well-characterized, low-mass, sub-Gyr, stellar-mass eclipsing binaries, which constitute some of the strongest observational tests of stellar evolution theory at low masses and young ages.